Tata Ruang Zona Tengah Di Desa Tenganan Pegringsingan : Kajian Arkeologi Keruangan - Miasih, Ni Ketut; Srijaya, I Wayan; Widya Paramadhyaksa, I Nyoman (Humanis; Volume 16. No. 1. Juli 2016, 2016)
Settlement archaeology investigated of archaeological site or human place for living by all type of their daily activities. Settlement archaeology also explain about spatial that is sub-explanation from the settlement investigation. Spatial archaeology is one of the specific research in archaeology investigation which is focus in concerning investigate of spatial dimension, thing, and shape dimension.Spatial arrangement of Tenganan pegringsingan village has a partitioned pattern, straight from the north to the south or arranged linearly. Tenganan village is one of the old village in Bali which is keep holding a megalitik tradition that is still fungtioned till present. The reseach problem in this research is about building typology in center spatial of Tenganan pegringsingan village and zon e image that is formed in the center spatial base on the function. The theory that is used in this research is structural-functional theory and sacred profane theory. The method that is used to answer the problem that had been formulated in this research concerned about the step to collect the data, there are by observation, interview, book review. The next step is about processing the data by etno-archaeology analysis, quality analysis, spatial analysis, context analysis, and behavior analysis. The analysis of the problems formulated above is as follows. In the building typology, devided into 2 parts, that are sacred  building and profane building. From the side of the building pattern, material also architecture, there is applied a traditional architecture by simple pattern without any ornament, decoration, and any other variation of aesthetics. From the zon e that is formed in the middle zone, there are three awangan. There are awangan kauh, awangan tengah, and awangan kangin. The daily activities are done in the middle zone, both of the social activity and culture activity.